Unveiling the factors influencing science teachers' adoption of eye-tracking technology through the GETAMEL framework - Özdemir, Alper Murat (Frontiers in Education, 2025)
IntroductionEye-tracking technology offers valuable insights into learners' cognitive and behavioral engagement, yet its classroom adoption by science teachers remains limited. This study explores the factors affecting science teachers' readiness and intention to integrate eye-tracking into their instructional practices.MethodsUsing the General Extended Technology Acceptance Model for E-Learning (GETAMEL) as the theoretical framework, data were collected from 800 in-service science teachers via structured questionnaires. The analysis employed structural equation modeling to test hypothesized relationships among model constructs.ResultsResults indicate that subjective norm, perceived enjoyment, experience, self-efficacy, and anxiety significantly influence perceived usefulness (R2 = 0.38) and perceived ease of use (R2 = 0.43). These perceptions, in turn, affect attitudes and behavioral intentions (R2 = 0.52) toward adopting eye-tracking technology.DiscussionThe findings underscore the importance of emotional, cognitive, and contextual factors in shaping teachers' adoption behavior. Implications are discussed for designing teacher training programs, educational policies, and curriculum strategies that support the integration of eye-tracking tools in science education.